Economic effects analysis of public investment in road improvement works in Hokkaido. Simulation analysis based on a macro-econometric model of Hokkaido - Hideaki Abe; Tatsuhide Ito; Toshio Kuroyanagi; Hiroki Katagiri; Izumi Akihiro; Wada Tadayuki (European Regional Science Association (ERSA), 2002)
The objective of this study is to clarify how public investment in road improvement projects over a given analytical period of time has affected Hokkaido`s economic structure on the whole in relation to the industrial economy, prefectural income, household consumption, and commodity prices, through a simulation analysis based on a macro-econometric model. More specifically, our goal is to model both the direct effects achieved through the use of improved roads including the reduction of time-distance coefficients, the reduction of transportation costs and market expansion, and the indirect effects such as enhancement of lifestyles and convenience and influence on other public projects including living area improvement and promotion of regional areas, and to identify these effects quantitatively. Taking data availability into consideration, this study covers a 21-year analysis period covering the years 1976 through 1996. In constructing a quantitative model, the effect flow to be modeled was examined from two perspectives: 1) an effect flow showing the effects of road improvement works on production efficiency and market efficiency; and 2) an effect flow showing the effects of road improvement works on living standards considering convenience and lifestyle improvement. Then we attempted building a model that could indicate the occurrence of these effects in both Flow and Stock contexts. As a result of the simulation analysis, it was clarified that application of road improvement works would bring about pronounced positive economic benefits in tertiary industries, particularly in the transportation-service and wholesale/retail sectors, and greatly expand the prefectural net product on the whole. It was also revealed that these expansion effects would stimulate an increase in the prefectural income and in private final consumption expenditure. Furthermore, a simulation analysis on the economic effects that the expansion of the express-highway network would have on Hokkaido`s entire economy revealed that there would be a large effect particularly on investment and production within the transportation/communication industry and also on the commercial output of the wholesale/retail industry.
Keywords: 330